2004
DOI: 10.1002/chin.200442046
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Oxidation of Thiols to Disulfides Catalyzed by Trichlorooxyvanadium.

Abstract: Oxidation O 0212Aerobic Oxidation of Thiols to Disulfides Catalyzed by Trichlorooxyvanadium.-Oxidative coupling of several kinds of thiols (I) to disulfides (II) is carried out in the presence of a molecular sieve and the title catalyst in aprotic polar solvents. The disulfides are efficiently obtained, although in relatively slow reaction rates. The coupling reaction can be accelerated by using higher amounts of the catalyst. Remarkably, mercaptoethanol (Ic) is much faster oxidized than the other thiols. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…141 It should be mentioned here that bromination reactions of C-C multiple bonds, aromatic compounds and diketones have been performed with the bromonium ion as obtained by selective oxidation of bromide with H 2 O 2 in the presence of tantalum chloride. 142…”
Section: Activation Of S-containing Compoundsmentioning
confidence: 99%
“…141 It should be mentioned here that bromination reactions of C-C multiple bonds, aromatic compounds and diketones have been performed with the bromonium ion as obtained by selective oxidation of bromide with H 2 O 2 in the presence of tantalum chloride. 142…”
Section: Activation Of S-containing Compoundsmentioning
confidence: 99%
“…During the course of our study of the tantalum(V)-catalyzed oxidation of halogen anions to halogen cation equivalents, [6][7][8] we found that 1,3-diphenylpropane-1,3-dione could be quantitatively monobrominated by treatment with TaCl 5 (0.1 equiv), KBr (8.0 equiv), H 2 O 2 (8.0 equiv) and aqueous HCl (8.0 equiv) in chloroform. 6 We further examined the reaction, and found that the monobrominated compound could be obtained in the absence of the tantalum(V) catalyst. The most appropriate conditions are the treatment of 1 with KBr (5.0 equiv), HCl (5.0 equiv), and H 2 O 2 (20.0 equiv) in toluene at room temperature with stirring by a magnetic stirrer (Table 1).…”
mentioning
confidence: 99%
“…6 We further examined the reaction, and found that the monobrominated compound could be obtained in the absence of the tantalum(V) catalyst. The most appropriate conditions are the treatment of 1 with KBr (5.0 equiv), HCl (5.0 equiv), and H 2 O 2 (20.0 equiv) in toluene at room temperature with stirring by a magnetic stirrer (Table 1).…”
mentioning
confidence: 99%